2012
DOI: 10.3109/14647273.2012.723838
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate maternal weight gain in singleton and twin pregnancies: what is the evidence?

Abstract: A review of the literature on maternal weight gain in singleton and twin pregnancies has identified two main messages. Firstly, that very little robust evidence exists on which to base advice to mothers about appropriate weight gain during pregnancy. Evidence that does exist has tended to be observational, or based on under-powered intervention studies and unable to provide definitive conclusions. Secondly, that although specific weight gains have been recommended by the Institute of Medicine (IOM) in the USA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…These were later updated in 2009, on the basis of the recorded interquartile range of weight gain from a study of females delivering twins after more than 36 weeks of gestation [1]. However, these guidelines for twin pregnancies have been questioned and have been referred to as "provisional standards" [11,12]. Moreover, studies analyzing these guidelines have presented conflicting results demonstrating that women who gain weight beyond the IOM guidelines achieve healthy pregnancy outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were later updated in 2009, on the basis of the recorded interquartile range of weight gain from a study of females delivering twins after more than 36 weeks of gestation [1]. However, these guidelines for twin pregnancies have been questioned and have been referred to as "provisional standards" [11,12]. Moreover, studies analyzing these guidelines have presented conflicting results demonstrating that women who gain weight beyond the IOM guidelines achieve healthy pregnancy outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these guidelines for twin pregnancies have been questioned and have been referred to as "provisional standards" [11,12]. Moreover, studies analyzing these guidelines have presented conflicting results demonstrating that women who gain weight beyond the IOM guidelines achieve healthy pregnancy outcomes [12,13]. Studies have also indicated that excessive weight gain in may improve neonatal birth weight without worsening maternal outcomes [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study may be helpful for Japanese women with multifetal pregnancies. However, it should be noted that "appropriate gestational weight gain" is not indicated in this study because of the nature of this study, as Leese et al [9] pointed out.…”
Section: Discussionmentioning
confidence: 86%
“…Colleagues in the United Kingdom take a far different approach to weight management in pregnancy, although both the United Kingdom and the United States use BMI as the standard measure for obesity 6,7 Citing the lack of evidence on which to base advice, the Royal College of Obstetricians and Gynaecologists (RCOG) instead opts to identify the sources of increased weight in pregnancy (Table 3). Colleagues in the United Kingdom take a far different approach to weight management in pregnancy, although both the United Kingdom and the United States use BMI as the standard measure for obesity 6,7 Citing the lack of evidence on which to base advice, the Royal College of Obstetricians and Gynaecologists (RCOG) instead opts to identify the sources of increased weight in pregnancy (Table 3).…”
Section: Interventionsmentioning
confidence: 99%
“…The methodological quality of all of the studies was rated poor to fair. 6 The IOM provides only provisional recommendations for twin gestations (Table 5). In the Campbell analysis noted above, 5 quantitative studies were pooled and also found no effect on GWG.…”
Section: Antepartum Testingmentioning
confidence: 99%